DISTRIBUCION ESTACIONAL DE LOS TABANOS EN LA RESERVA NACIONAL RIO CLARILLO, CHILE-CENTRAL (DIPTERAtTABANIDAE) - González, Christian R. (Acta Entomológica Chilena, 2022)
Nine genera and nineteen species of horse flies (Díptera : Tabanidae) were caught in the National Reserve of Río Clarillo near Santiago (33s 51’ Lat. S - 70Q 29’ Long. W). The specimens were collected with net since January 1990 to December 1991. Scaptia (Pseudoscione) viridiventris (Macquart) joined S.(P.) vittota (Philippi) are the most abundant species. Tabanid abundance was greater in November (1990) and January (1991); number of species was greater between December to January (thirteen species). No horse flies were caught at the site after mid-March until September (fall - winter season). Only one specimen was caught of Esenbeckia (Palassomyia) fascipennis (Macquart), Mesomyia (Coracellci) carbo (Macquart), Dasybasis (Agelanius) paulseni mapuche Coscaron & Philip and Tabanus claripennis (Bigot).